Kemampuan Riil dan Tertaksir Sifat Produksi dan Reproduksi Sapi Perah di KAN Jabung - Y. N. Zulfa; R. R. Noor; A. Atabany (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2022)
Production and reproductive characteristics affect the productivity of dairy cows in producing milk. The repeatability value uses to estimate the most probable producing ability (MPPA), which helps estimate the productivity of dairy cattle in the subsequent lactation period. The study aimed to determine the actual ability and accuracy of MPPA based on dairy cows’ reproductive and production characteristics. Secondary data from 124 Friesian Holstein dairy cows under the auspices of the Jabung Agro Niaga Cooperative, Malang Regency. The t-test compares data from the 3rd lactation period and the MPPA value. T-test results between MPPA and 3rd lactation of milk production 0.436; lactation length 0.387; dry period 0.051; DO 0.3; and CI 0.243. The five traits are more than 0.05, so they can be stated to be significantly the same as the real value in 3rd lactation. The results of the t-test for postpartum mating are 0.04 and S/C 0.002, significantly different from the actual value in the third lactation because it is less than 0.05. Based on the research results, the MPPA method accurately estimates the characteristics of lactation length, 305 days of milk production, dry period, days open (DO), and calving interval (CI).